1916
DOI: 10.1093/infdis/19.3.395
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Amebic Dysentery in Monkeys

Abstract: This article records a spontaneous outbreak of a disease in monkeys in which the lesions corresponded closely to those found in amebic or tropical dysentery in man, and in which protozoal organisms occurred that had the structure and characteristics of those amebas generally considered the causative agents in human tropical dysentery. This spontaneous outbreak of amebic dysentery is of special interest since there appears to be no record of a similar case, and because our knowledge of this disease in animals i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1923
1923
1989
1989

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…34 Although not the first paper on amebiasis in monkeys, the work was characterized by a clear and wellillustrated description of both the gross and histologic lesions in the intestinal tract and liver. It was a work of exceptional quality for the Pathological Division, because it actually dealt with the disease process rather than exclusively with the organism that caused it.…”
Section: Amentioning
confidence: 99%
“…34 Although not the first paper on amebiasis in monkeys, the work was characterized by a clear and wellillustrated description of both the gross and histologic lesions in the intestinal tract and liver. It was a work of exceptional quality for the Pathological Division, because it actually dealt with the disease process rather than exclusively with the organism that caused it.…”
Section: Amentioning
confidence: 99%
“…Infection is said to be common in Old World monkeys but uncommon or rare in New World monkeys obtained from their natural habitat [200,742,791,869]. Young monkeys and New World monkeys are reported to sustain more severe lesions from infection with this parasite [46,90,207,223,704,742,869]. The morphology of this parasite has been discussed [90,182,290,389,529,530,748,791].…”
Section: Amebiasismentioning
confidence: 99%
“…Only when it invades the mucosa does it become pathogenic and may lead to amebic dysentery [529]. Clinically, affected animals show the following signs: lethargy, weakness, dehydration, anorexia, vomiting, and severe diarrhea that mayor may not be hemorrhagic or catarrhal [90,223,290,379,385,461,530,588,665,704,829,868,869,890]. The gross and microscopic lesions associated with amebiasis in nonhuman primates have been described [57,60,90,290,300,461,588,665,704,742,791,829,869].…”
Section: Amebiasismentioning
confidence: 99%
“…One case is on record of dysentery, which may have been amcebic, ill i~ captive orang-outang in the Dutch West Indies (Prowazek (1912 b ) ) . 'L'lien there was the dysentery outbreak among captive spi'der-monkeys in tropical South America, reported by Eichhorn and Gallagher (1916), which resulted in the death of eight animals : the authors found lesions in the intestine and liver, and they reported amcebz, which they regarded as the cixrisativc organism but which did not produce dysentery when put into cats. (13iit, see footnote on p.…”
Section: Amahzmentioning
confidence: 99%